The integration of ICT in higher education in French-speaking West African countries, mythes and reality : the case of Senegal - (:unkn) unknown (My University, 2022)
This research work focuses on the integration of ICT in higher education (TICE) in French-speaking West African countries. It is thought out within the scientific traditions that exist in Information and Communication Sciences (CIS) and focusing on ICT integrated into societal and educational spheres. We were particularly interested in the discourse analysis approach, of which the work of Simone Bonnafous is often considered as pioneering, to study the question of the integration of ICT in these countries, as well as the utopias, logics and myths that the related speeches convey. So through a "macrosociological" analysis of the integration of ICT in higher education, according to a discursive approach relating to the official texts and reports of the main donors and actors in the field (AUF, World Bank, UNESCO, UEMOA, etc.). ), we were interested in the games and strategies of the different actors present (international organizations, States and higher education establishment). We integrated into the analysis a mesoscopic and microsociological dimension relating firstly to the public policies put in place in the field of ICT in Senegal, and then on the practices and uses of the tools and devices of distance training set up in Senegal. level of three target institutions (UVS, EBAD, ESP). The objective was therefore to confront the political and ideological discourse of international organizations with the reality on the ground to finally see whether ICTs were a myth or a reality in public universities in French-speaking West African countries in general and from Senegal in particular
Keywords: African Research